ENHANCING CYBERSECURITY IN WIRELESS SENSOR NETWORKS: ROLE OF ADVANCED DATA COMMUNICATION PROTOCOLS - Verma, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Wireless Sensor Networks (WSNs) are essential to contemporary data-centric ecosystems, facilitating vital applications in healthcare, smart cities, environmental monitoring, and defense. Nonetheless, the escalating intricacy of these networks, along with their resource-limited nodes, renders them susceptible to a wide array of cybersecurity attacks. This study examines the impact of sophisticated data transfer protocols on the security and resilience of wireless sensor networks (WSNs). Through the analysis of the efficacy of protocols such as Zigbee, Bluetooth Low Energy (BLE), and IEEE 802.15.4 in countering threats like eavesdropping, node capture, and denial of service, we ascertain optimal practices for protocol selection and execution. Furthermore, we evaluate the efficacy of adaptive routing, data encryption, and authentication methods in enhancing data integrity, secrecy, and network availability. The findings emphasize the need of protocol enhancements in protecting WSN data transmission, providing insights into scalable and secure communication frameworks vital for next-generation IoT applications.